OCT and OCTA in retinal disorders - Ehlers, Justis P.; Mehta, Nitish; Abraham, Joseph; Le, Thuy K.; Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer, 2021)
'Highly visual and easy to navigate, OCT and OCT Angiography in Retinal Disorders is a concise, reliable reference for optical coherence tomography (OCT) and OCT angiography findings in both common and uncommon retinal disorders. Each chapter explores the prognostic features of OCT and OCTA scans along with additional diagnostic modalities for comparison and correlation. Where appropriate, longitudinal changes in response to treatment or natural history are also discussed. Includes hundreds of high-quality, striking images. Highlights the salient imaging features of the clinical entity or entities being discussed. Covers OCT technology, techniques, and scanning patterns . Provides concise, authoritative guidance on numerous key areas in retinal disease, including retinal vascular disease, inflammation, retinal degenerations and dystrophies, ocular trauma ocular tumors, and much more'--
Retinal vascular disease -- Outer retinal and choroidal disease -- The vitreoretinal interface and peripheral retinal pathology -- Inflammation and infection -- Inherited retinal degenerations -- Retinal, choroidal, and scleral lesions -- Ocular trauma -- Intraoperative and postoperative imaging -- Drug toxicities -- Imaging of the optic nerve.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Retinal Diseases -- diagnostic imaging; Tomography, Optical Coherence -- methods; Retinal Vessels -- diagnostic imaging; Angiography -- methods; Diagnostic Techniques, Ophthalmological; Retina -- Diseases -- Diagnostic imaging; Angiography